2018
DOI: 10.3390/genes9080376
|View full text |Cite
|
Sign up to set email alerts
|

Origins Left, Right, and Centre: Increasing the Number of Initiation Sites in the Escherichia coli Chromosome

Abstract: The bacterium Escherichia coli contains a single circular chromosome with a defined architecture. DNA replication initiates at a single origin called oriC. Two replication forks are assembled and proceed in opposite directions until they fuse in a specialised zone opposite the origin. This termination area is flanked by polar replication fork pause sites that allow forks to enter, but not to leave. Thus, the chromosome is divided into two replichores, each replicated by a single replication fork. Recently, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(75 citation statements)
references
References 55 publications
3
72
0
Order By: Relevance
“…They found that this mutant carried a ~0.8 Mb inversion spanning the ter (J. Dimude et al 2018). However, this mutant grew slowly.…”
Section: Resultsmentioning
confidence: 99%
“…They found that this mutant carried a ~0.8 Mb inversion spanning the ter (J. Dimude et al 2018). However, this mutant grew slowly.…”
Section: Resultsmentioning
confidence: 99%
“…In the initial analysis, the doubling time of oriC + oriZ + and wild type cells was found to be similar (Wang et al, 2011). However, when we measured the doubling times for MG1655 and oriC + oriZ + constructs in direct comparison, we found that oriC + oriZ + cells grew slightly slower in two independent studies (∼21 min in comparison to ∼20 min in wild type cells) (Ivanova et al, 2015;Dimude et al, 2018b).…”
Section: Introducing a Second Origin Into The E Coli Chromosomementioning
confidence: 87%
“…Whereas the previous studies by Ivanova et al and Dimude et al, (45,46) isolated structural variations while creating the parent strain, we were able to isolate our suppressors only after 4 to 8 days of selection in a laboratory evolution experiment.…”
Section: Discussionmentioning
confidence: 70%
“…Dimude et al (46) placed a second ori, termed oriX, counterclockwise of oriC. They found that this mutant carried an ϳ0.8-Mb inversion spanning the ter (46). However, this mutant grew slowly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation